2019
DOI: 10.1182/bloodadvances.2018024075
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and interim functional imaging with PET effectively risk stratifies patients with peripheral T-cell lymphoma

Abstract: The prognosis of peripheral T-cell lymphoma (PTCL) is heterogenous. Baseline or interim imaging characteristics may inform risk-adapted treatment paradigms. We identified 112 patients with PTCL who were consecutively treated with cyclophosphamide, doxorubicin, vincristine, prednisone (CHOP)/CHOP-like regimens with the intent to consolidate with an autologous transplant. Baseline (n = 93) and interim (after 4 cycles, n = 99) positron emission tomography (PET) images were reevaluated, and we calculated baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 35 publications
6
35
1
Order By: Relevance
“…Our results confirm the strong prognostic value of baseline TMTV in patients with PTCL, and patients with a TMTV greater than 228.8 cm 3 had lower survival. This result is consistent with the results of published studies [11,12]. In the study of Cottereau et al, the baseline TMTV (cutoff value of 230 cm 3 ) was found to be the only significant independent predictor for both PFS (P = 0.013) and OS (P = 0.021) [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results confirm the strong prognostic value of baseline TMTV in patients with PTCL, and patients with a TMTV greater than 228.8 cm 3 had lower survival. This result is consistent with the results of published studies [11,12]. In the study of Cottereau et al, the baseline TMTV (cutoff value of 230 cm 3 ) was found to be the only significant independent predictor for both PFS (P = 0.013) and OS (P = 0.021) [11].…”
Section: Discussionsupporting
confidence: 91%
“…In the study of Cottereau et al, the baseline TMTV (cutoff value of 230 cm 3 ) was found to be the only significant independent predictor for both PFS (P = 0.013) and OS (P = 0.021) [11]. Mehta-Shah et al 's study also showed that a high baseline TMTV (cutoff value is 125 cm 3 ) predicted worse OS (HR 6.025; P = 0.022) and EFS (HR 3.861; P = 0.005) [12]. TMTV is a measure of the viable tumor fraction and may better represent the metabolic burden of tumors.…”
Section: Discussionmentioning
confidence: 89%
“…18 Moreover, TLG in combination with iPET more accurately predicted survival in PTCL. Mehta-Shah et al recently reported on the analysis of iPET and TMTV in PTCL, 28 indicating that the use of TMTV allowed for the further classification of patients with favorable prognoses into subgroups of excellent and poor prognoses. Notably, favorable characteristics (low TMTV and negative iPET results) could be used to identify groups with a 5-year event-free survival rate exceeding 60%.…”
Section: Discussionmentioning
confidence: 99%
“…The results among studies might be inconsistent due to the different thresholds used for delineating tumors. In some studies, the absolute threshold of an SUV ≥3.0 or 2.5 was used to calculate MTV [12,[25][26]] and proved to be easiest to apply in clinical settings. [27] In addition, PTCL are heterogeneous in their FDG-uptake, and TMTV estimated using xed value thresholding (SUV≥3.0 or 2.5) may re ect the total tumor burden more accurately.…”
Section: Discussionmentioning
confidence: 99%